Victims made invisible: The children of Tacna and Arica under Chilean occupation (1880- 1929) - Miranda Wilson, Giannina (2025)
The children of Tacna and Arica played a fundamental role during the Chilean occupation. Children were seen as future voters in an eventual plebiscite, making their literacy and cultural adhesion indispensable, and the management of their education a constant dispute. Some of these children joined the Peruvian resistance and suffered reprisals from the occupying authorities. In general terms, children were the victims made invisible by the Chileanization campaign, and also victims of the Peruvian government’s failure to guarantee their protection.